Correlations among lymphocyte count, white matter hyperintensity and brain atrophy in patients with ischemic stroke - Liu, Chenchen; Shi, Dai; Ni, Xiaoqiong; You, Shoujiang; Wu, Xiaofen; Zhuang, Sheng; Cai, Wu; Xu, Liang (Frontiers in Aging Neuroscience, 2025)
BackgroundWhite matter hyperintensity (WMH) and brain atrophy, as imaging marker of cerebral small-vessel diseases (CSVD), have a high prevalence and strong prognostic value in stroke. We aimed to explore the association between lymphocyte count, a maker of inflammation, and WMH and brain atrophy in patients with acute ischemic stroke (AIS).MethodsA total of 727 AIS patients with lymphocyte count and brain magnetic resonance imaging data were enrolled. Participants were divided into four groups according to the quartiles of baseline lymphocyte counts. WMH is frequently divided into periventricular hyperintensity (PVH) and deep white matter hyperintensity (DWMH). WMH was defined as Fazekas scale score ≥ 3; PVH was defined as periventricular Fazekas scale ≥2; DWMH was defined as deep Fazekas scale ≥2. Brain atrophy was defined as global cortical atrophy score ≥ 1. Multivariable logistic regression models were used to assess the association between lymphocyte count and WMH and brain atrophy.ResultsAmong 727 AIS, 517 (71.1%), 442 (60.8%), 459 (63.1%), 583 (80.2%) had WMH, PVH, DWMH and brain atrophy, respectively. After adjustment for potential covariates, the highest quartiles of lymphocyte counts were significantly associated with lower risk of WMH (adjusted odds ratio [aOR] 0.57, 95% confidence intervals [CI] 0.32–0.99), PVH (aOR 0.52, 95% CI 0.31–0.87), DWMH (aOR 0.53 95% CI 0.32–0.90) as well as brain atrophy (aOR 0.46, 95% CI 0.23–0.92) compared with the lowest quartiles of lymphocyte counts, respectively. Furthermore, a notable inverse association was observed between continuous lymphocyte counts and WMH, PVH, DWMH, and brain atrophy. Additionally, we found that the inverse association between baseline lymphocyte count and WMH was significant only in individuals with mild stroke.ConclusionIn patients with AIS, there was an independent and inverse association between the baseline lymphocyte count and both WMH and brain atrophy.